A case study in modeling a human-intensive, corporate software process - Barghouti, N.S.; Rosenblum, D.S. (Third International Conference on the Software Process : applying the software process : proceedings, October 10-11, 1994, Reston, Virginia, 1994)
Describes a case study whose objective was to determine the feasibility, utility and limitations of using a process support tool to model and analyze a real process in active use by a large software development organization. The subject of our study was a process used in the maintenance of the AT&T 5ESS switching system software. The process was interesting to study primarily because it is a human-intensive process, which makes it less amenable to automation than build-like processes. Marvel 3.1 was used to create an executable model of the process. A key feature of our model is the separation of the informational aspects of the process from its operational aspects. The Marvel environment can be used for simulation, guidance, and tracking and querying the state of the process as it is performed. One of the key lessons learned from the study was that a complete process model must include an information model as well as the traditional activity model.< >